2013
DOI: 10.1111/geoj.12031
|View full text |Cite
|
Sign up to set email alerts
|

Geographical barriers to education law advice: access, communications and public legal services in England and Wales

Abstract: In line with changes to the delivery of other public services, current reforms to publicly funded legal advice services within England and Wales seek to move services from traditional face-to-face settings to delivery predominantly over the telephone. Government justification for the policy has focused on greater equality of access. In contrast, criticisms have centred upon the inability of the telephone to address the needs of certain client groups or complex cases. Using administrative records collected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Currently there is little other academic literature which explicitly focuses on the significance of place in relation to social welfare law advice in England and Wales. Recent statistical analysis of Legal Services Commission (LSC) data comparing telephone-only and face-to-face education law advice shows that the further away a client is from their nearest provider the more likely they are to use telephone advice (Patel, Balmer & Smith, 2014). The same research also found that telephone advice is less likely to provide a tangible outcome for the client, largely because of a greater propensity for face-to-face cases to be taken further by the adviser.…”
Section: About This Studymentioning
confidence: 99%
“…Currently there is little other academic literature which explicitly focuses on the significance of place in relation to social welfare law advice in England and Wales. Recent statistical analysis of Legal Services Commission (LSC) data comparing telephone-only and face-to-face education law advice shows that the further away a client is from their nearest provider the more likely they are to use telephone advice (Patel, Balmer & Smith, 2014). The same research also found that telephone advice is less likely to provide a tangible outcome for the client, largely because of a greater propensity for face-to-face cases to be taken further by the adviser.…”
Section: About This Studymentioning
confidence: 99%